MEDIA BASED ON STUDENT PARTICIPATION IN LEARNING - Juwita; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research aims to explore the steps in developing an effective learningsystem design model. The method that is often used is the qualitativeexperimental method, namely a research method that aims to explain andpredict what will happen to a variable if it is given certain treatment to othervariables. The learning system guarantees learning activities by formulatingclass-oriented teaching and learning activities that emphasize the good use oftechnology and media to create active and meaningful learning for students.The purpose of writing this article is to explain the stages in the sure learningdesign model. The methods and media used in data collection focus onemphasizing teaching to students. The research results showed that the stagesin the email learning system design model consisted of 6 (six) steps, namely:Analyzing Students, Stating Goals, Selecting Methods, Media and Materials,Utilizing Media and Materials, Requiring Student Participation, Evaluating andRevising.